Planning, Practice, and Achievement of Sports Programs in Secondary Schools of Butwal Municipality - Acharya, Shankar Prasad (SNPRC Journal, 2025)
This study is entitled planning, practice, and achievement of sports programs in secondary schools of Butwal Municipality. The main purpose of this study is to assess the planning and implementation of sports programs and evaluate their practice and achievements. This research is a descriptive study conducted in Butwal Sub-Metropolitan City, covering all secondary schools in the area. The total population consists of 61 institutions, including 22 publics and 39 private schools. From this population, 22 schools were selected by using a simple random sampling method. To ensure a balanced comparison, the sample was divided into 11 public and 11 private schools. Data were collected from headmasters, physical education teachers, and sports teachers using structured interviews and observation checklists, and were analyzed using descriptive ways with simple statistics like percentage and mean. The findings revealed that although all schools reported having annual sports programs, planning often lacked detail and consistency. Sports practices were irregular and insufficiently supervised, which limited student participation and reduced achievements beyond the school level. The Public schools were more constrained by financial shortages, whereas private schools faced greater challenges like inadequate physical facilities. Across both groups, common issues included a shortage of trained personnel, weak management, administrative difficulties, and low student motivation. The study concludes that systematic planning, adequate resource allocation, and effective monitoring are necessary to enhance the quality and outcomes of school sports programs. Strengthening these areas can promote wider space for student participation, improve performance, and support the overall physical, social, and skill development of secondary school students.